Investigation protocols for onsite assessment of floor and wall components in historical school buildings - Mariella De Fino (Tema, 2016)
The paper is going to describe a methodological framework for onsite non-destructive investigation of materials, construction components, residual performances and state of conservation of historical-architectural school buildings. In detail, some operation protocols are proposed and validated as decision-making support tools for radar scanning and thermography of floor and wall components in buildings of the early XX century, in order to achieve reliable and meaningful identification of the actual characteristics and anomalies and, thus, address compatible and low invasive maintenance measures.